Polyester-based pressure-sensitive adhesive composition, polyester-based pressure-sensitive adhesive, and pressure-sensitive adhesive sheet
A polyester adhesive composition with a lower acid value polyester resin and inorganic filler addresses the challenge of achieving high refractive index and stability, providing excellent adhesion and transparency for optical components in liquid crystal displays.
Patent Information
- Application Number
- JP2023128487
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-09-26
- Filing Date
- 2023-08-07
- Publication Date
- 2025-01-15
- Estimated Expiration
- 2039-08-29
AI Technical Summary
Existing polyester adhesive compositions used in optical components for liquid crystal displays face challenges in achieving high refractive index while maintaining solution stability, transparency, and good coating properties, as adding inorganic oxides can lead to gelation and poor dispersibility.
A polyester adhesive composition is formulated with a polyester resin having a lower acid value and incorporating ionic groups, combined with an inorganic filler, to enhance refractive index, compatibility, and stability, using specific polyhydric carboxylic acids and polyhydric alcohols to balance adhesive strength and refractive index.
The composition achieves excellent adhesion to glass, high refractive index, and good transparency, suitable for optical components, with improved solution stability and coating properties, enhancing light extraction efficiency in liquid crystal displays.
Smart Images

Figure 0007613515000001 
Figure 0007613515000002 
Figure 0007613515000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a polyester-based pressure-sensitive adhesive composition, a polyester-based pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet. More specifically, it has excellent adhesive strength when used as a polyester-based adhesive, and also has an inorganic filler. Polyester-based with excellent dispersibility, excellent solution stability and transparency of coating liquid, and good coatability. The present invention relates to a pressure-sensitive adhesive composition, and further to a polyester-based pressure-sensitive adhesive and a pressure-sensitive adhesive sheet. [Background technology]
[0002] Traditionally, polyester resins have been used because of their excellent heat resistance, chemical resistance, durability, and mechanical strength. , films, PET bottles, fibers, toner, electrical parts, and adhesives and pressure sensitive adhesives. It is used for a variety of purposes.
[0003] In recent years, LCD (Liquid Crystal Display) play) or in combination with such display devices as touch panels Input devices are becoming more widely used, and their manufacture requires optical films and Transparent pressure-sensitive adhesive sheets are used to bond optical members such as substrates.
[0004] Furthermore, a light diffusion sheet is used to improve the visibility of the liquid crystal display device. The material is made of a transparent resin and a filler, and the difference in refractive index between the resin and the filler is utilized. The optical members of the liquid crystal display device are made of adhesive. It is desirable for the refractive index of the adhesive layer to be higher in order to improve light diffusion properties. In addition, the refractive index of the optical film is generally higher than that of the adhesive, so reflection occurs at the interface. This causes a problem that the light extraction efficiency of the display device is reduced. By eliminating the adhesive, the interface reflection is reduced, and the light extraction efficiency is improved. A higher refractive index is desired.
[0005] Acrylic resin adhesives are generally used to bond the above optical components. However, the refractive index of the adhesive layer is about 1.47, and a high refractive index exceeding 1.50 is not possible. It has no refractive index. Therefore, Patent Document 1 proposes a polyester-based adhesive instead of an acrylic resin adhesive. It has been proposed. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-25575 A Summary of the Invention [Problem to be solved by the invention]
[0007] However, in the technology disclosed in the above Patent Document 1, the adhesive composition has a certain degree of high refractive index. The film contains a polyester resin having a high light diffusion rate. From the standpoint of light extraction efficiency, there is a demand for polyester-based pressure-sensitive adhesive compositions with even higher refractive indexes.
[0008] Generally, a method for improving the refractive index of a resin is to add an inorganic oxide. However, simply blending an inorganic oxide into a polyester resin may result in a loss of elasticity from the resin composition. The coating liquid may gel, resulting in insufficient coating properties, or poor dispersibility. The coating liquid or coating film becomes cloudy due to poor refractive index. However, a pressure-sensitive adhesive composition having excellent solution stability, transparency and coatability has not yet been obtained.
[0009] In this way, by blending inorganic fillers such as inorganic oxides with polyester resin, This can provide a high refractive index and various other functions, but at the same time, it can also affect the solution stability of the coating liquid. There is an increasing demand for pressure-sensitive adhesive compositions that are excellent in properties and transparency and have good coatability.
[0010] In the present invention, under such circumstances, the adhesiveness when a polyester-based adhesive is used is improved. It has excellent coating strength, and is excellent in solution stability and transparency while providing various functions. The present invention provides a polyester-based pressure-sensitive adhesive composition having excellent adhesion, a polyester-based pressure-sensitive adhesive, and a pressure-sensitive adhesive sheet. The purpose of this document is to provide [Means for solving the problem]
[0011] However, the present inventors have conducted extensive research in light of the above circumstances and have found that polyester resins and In the polyester-based pressure-sensitive adhesive composition containing an inorganic filler, The acid value of polyester resin is lower than that of polyester resins that are generally used. By selectively using a polyester resin, and by adding an ionic group to a polyester resin, By incorporating The present invention provides a polyester-based pressure-sensitive adhesive composition having excellent solution stability and transparency of a coating solution and good coatability. We have discovered and completed the present invention.
[0013] Books Invention No. 1 The gist of the present invention is that the composition contains polyester resin (A) and inorganic filler (B). The polyester-based adhesive composition is used to form a pressure-sensitive adhesive layer. An adhesive sheet, the above The polyester resin (A) is a polyester resin having a structural unit derived from a sulfonate group-containing dicarboxylic acid, Record The thickness of the adhesive layer Beyond 10μm 500μm below and The above adhesive sheet The adhesive layer is provided with a release sheet on the outside thereof, and is characterized in that the adhesive strength (α) is 5N / 25mm or more. Viscosity This concerns the receiving sheet. Adhesive strength (α): When a polyester-based adhesive is formed on a substrate to form an adhesive sheet, it is attached to a glass plate adherend and left for 30 minutes at 23°C and 50% RH, after which the 180-degree peel strength (N / 25 mm) is measured at a peel speed of 300 mm / min against the adherend.
[0016] As described above, for example, in order to improve the refractive index of a pressure-sensitive adhesive, In the above case, one of the methods to be considered is to mix inorganic oxides. In this case, The compatibility of such inorganic oxides with resins is important. For example, in the case of a general acrylic resin, It is difficult to achieve compatibility with adhesives that use oils, but by increasing the functional groups, It is possible to design to improve compatibility.
[0017] On the other hand, even in the case of polyester resins, compatibility can be improved by increasing the functional groups. However, it is difficult to introduce functional groups into the side chains of polyester resins, making them difficult to handle. Therefore, in polyester-based adhesives, the blending of such inorganic oxides is The law is difficult to adopt.
[0018] However, in the present invention, we have focused on the blending of such inorganic oxides and have conducted extensive research. As a result, by selecting a polyester resin with a relatively smaller acid value than usual, By incorporating ionic groups into polyester resins, a high refractive index can be achieved while It also has good compatibility, and the coating liquid has excellent solution stability and transparency, making it a polyester with good coatability. Thus, a polyester-based pressure-sensitive adhesive composition could be obtained. Effect of the Invention
[0019] The polyester-based pressure-sensitive adhesive composition of the present invention has excellent adhesion to adherends, particularly to glass. In addition, when used as a polyester-based adhesive, it has various functions while maintaining the solution stability and It has excellent transparency and good coatability, and is used for various adhesive sheets, especially for adhering optical components. It is useful as a laminating adhesive sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The configuration of the present invention will be described in detail below, but these are examples of preferred embodiments. It is something. In the present invention, the term "carboxylic acids" includes not only carboxylic acids but also carboxylic acids Carboxylic acid derivatives such as salts, carboxylic acid anhydrides, carboxylic acid halides, and carboxylic acid esters It also includes conductors.
[0021] The polyester-based pressure-sensitive adhesive composition of the present invention comprises a polyester-based resin (A) and an inorganic filler. It contains (B).
[0022] In the present invention, the polyester resin (A) is a polyester having an acid value of 3 mgKOH / g or less. At least one selected from ester resins and polyester resins containing ionic groups It is. The polyester resin (A) will be described below in detail.
[0023] <Polyester resin (A)> The polyester resin (A) used in the present invention contains polyvalent carboxylic acids ( (a1) and a copolymerization component containing a polyhydric alcohol (a2) That is why.
[0024] In addition, if the purpose is to increase the refractive index, a structural portion derived from an aliphatic polycarboxylic acid and an aromatic The fact that the adhesive contains a structural portion derived from an aromatic polyhydric alcohol provides a good balance between adhesive strength and refractive index. This is preferable in terms of the lance and the fact that the amount of the expensive inorganic filler (B) can be reduced. stomach.
[0025] [Polyvalent carboxylic acids (a1)] Examples of the polyvalent carboxylic acid (a1) used in the present invention include Malonic acid, dimethylmalonic acid, succinic acid, glutaric acid, adipic acid, trimethyladipic acid acid, pimelic acid, 2,2-dimethylglutaric acid, azelaic acid, sebacic acid, fumaric acid , maleic acid, itaconic acid, thiodipropionic acid, diglycolic acid, or any of these acids aliphatic dicarboxylic acids such as carboxylic acids; Terephthalic acid, isophthalic acid, benzylmalonic acid, diphenic acid, 4,4'-oxydibenzo Aromatic dicarboxylic acids such as benzoic acid, naphthalenedicarboxylic acid, or their derivatives kind; 1,3-Cyclopentanedicarboxylic acid, 1,2-Cyclohexanedicarboxylic acid, 1,3 -Cyclopentanedicarboxylic acid, 1,4-cyclohexanedicarboxylic acid, 2,5-norbornanedicarboxylic acid Alicyclic carboxylic acids such as lanthanedicarboxylic acid, adamantanedicarboxylic acid, or these carboxylic acids Aromatic dicarboxylic acids; and the like divalent carboxylic acids. These can be used alone or in combination of two or more.
[0026] Among these, it is preferable to contain aliphatic dicarboxylic acids in order to impart tackiness. It is particularly preferable that the dicarboxylic acid contains an aliphatic dicarboxylic acid having 4 to 12 carbon atoms. It is preferable to contain dipic acid and sebacic acids, and it is particularly preferable to contain sebacic acids. It is nice.
[0027] The content ratio of such aliphatic dicarboxylic acids to the total polyvalent carboxylic acids (a1) is The content is preferably 10 mol % or more, particularly preferably 30 to 95 mol %, and further preferably If the content is too low, the glass transition temperature becomes high. As a result, sufficient adhesive strength tends to be lost.
[0028] Among the above, aromatic dicarboxylic acids are preferred because they impart cohesive strength and increase the refractive index. Acids may also be included, for example isophthalic acids.
[0029] The content ratio of such aromatic dicarboxylic acids to the total polyvalent carboxylic acids (a1) is The content is preferably 90 mol % or less, particularly preferably 5 to 70 mol %, and further preferably If the content is too high, the glass transition temperature becomes high. As a result, sufficient adhesive performance tends to be unavailable.
[0030] In the present invention, from the viewpoint of a balance of adhesive properties, the polyvalent carboxylic acid (a1) is Aromatic dicarboxylic acids and aliphatic dicarboxylic acids can be used in combination, and the content ratio (mol The ratio is aromatic dicarboxylic acids / aliphatic dicarboxylic acids = 1 / 99 to 90 / 10. It is particularly preferable that the ratio of aromatic dicarboxylic acids to aliphatic dicarboxylic acids is 5. / 95 to 49 / 51, more preferably aromatic dicarboxylic acids / aliphatic dicarboxylic acids=1 It ranges from 0 / 90 to 30 / 70.
[0031] [Polyvalent carboxylic acids having ionic groups] In the present invention, in order to improve compatibility when adding the inorganic filler (B) described later, As the polyvalent carboxylic acid (a1), a polyvalent carboxylic acid having an ionic group is used. As the polyvalent carboxylic acid having such an ionic group, sulfur is particularly preferable. It is preferable to use sulfonate group-containing dicarboxylic acids. Dicarboxylic acids are monomers that have two carboxy groups and a sulfonate group in the molecule. As long as the component is not particularly limited, for example, sodium sulfonate or sulfone Phthalic acid, isophthalic acid, terephthalic acid, etc., containing alkali metal sulfonates such as potassium sulfonate The sulfonate group-containing carboxylic acids and their mono- or diesters are preferably used. The dicarboxylic acids can be used alone or in combination of two or more kinds.
[0032] Specific examples of the sulfonate group-containing dicarboxylic acids include 4-sulfoiso Sodium dimethyl phthalate, Sodium 5-sulfoisophthalate, 5-sulfoisophthalate Sodium dimethyl ester, potassium dimethyl 4-sulfoisophthalate, 5-sulfoisophthalate Potassium dimethyl thalate, Sodium 2-sulfoterephthalate, 2-sulfoterephthalic acid Potassium, Sodium 2-dimethylsulfoterephthalate, Dimethyl 2-sulfoterephthalate potassium salt, etc., and sodium 2-sulfoterephthalate diethylene glycol. Among these, sodium dimethyl 5-sulfoisophthalate is preferably used.
[0033] In addition, the proportion of polyvalent carboxylic acids having an ionic group in the polyvalent carboxylic acids (a1) is In this case, the amount is preferably 0.001 to 20 mol % based on the total amount of the polyvalent carboxylic acids (a1). It is preferable that the content is 0.01 to 10 mol %, more preferably 0.05 to 5 mol %, and particularly preferably 0.01 to 10 mol %. The content of the polyvalent carboxylic acid having an ionic group is preferably 0.5 to 2 mol %. If the amount is too large, the compatibility with the inorganic filler (B) described below when it is added will be low. If the amount is too high, the resin tends to become weak and the haze tends to increase (transparency decreases). The durability tends to decrease.
[0034] In order to increase the branching points in the polyester resin (A), trivalent or higher polyvalent carboxylates may be used. Acids can also be used. Examples of such trivalent or higher carboxylic acids include trimellitic acid and tricarboxylic acid, pyromellitic acid, adamantanetricarboxylic acid, trimesic acid, or any of these acids. Among them, trimellitic acid is preferred because it is relatively difficult to cause gelation. It is preferable to use:
[0035] The content ratio of such trivalent or higher polyvalent carboxylic acids is such that the cohesive strength of the adhesive is increased. In view of the above, it is preferable that the amount of the polyvalent carboxylic acid (a1) is 10 mol % or less, and particularly preferably 10 mol % or less, based on the total amount of the polyvalent carboxylic acid (a1). The content is preferably 0.1 to 5 mol %, and if the content is too high, the polyester resin ( A) is prone to gelation during production.
[0036] [Polyhydric alcohol (a2)] Examples of the polyhydric alcohol (a2) used in the present invention include Ethylene glycol, diethylene glycol, triethylene glycol, propylene glycol Recall, Dipropylene Glycol, 1,3-Propanediol, 2,4-Dimethyl-2 -Ethylhexane-1,3-diol, 2-methyl-1,3-propanediol, 2,2 -Dimethyl-1,3-propanediol (neopentyl glycol), 2-ethyl-2- Butyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol , 1,6-Hexanediol, 3-Methyl-1,5-pentanediol, 2,2,4-Trimethyl- Aliphatic diols such as trimethyl-1,6-hexanediol; 1,2-Cyclohexanedimethanol, 1,3-Cyclohexanedimethanol, 1,4 -Cyclohexanedimethanol, Spiroglycol, Tricyclodecanedimethanol, A Damantanediol, 2,2,4,4-tetramethyl-1,3-cyclobutanediol, etc. of alicyclic diols; 4,4′-thiodiphenol, 4,4′-methylenediphenol, bisphenol S, Bisphenol A, bisphenol fluorene, 4,4′-dihydroxybiphenyl, o -, m- and p-dihydroxybenzene, 2,5-naphthalenediol, p-xylenediol aromatic diols such as diol; and aromatic diols such as their ethylene oxide and propylene oxide adducts; and the like dihydric alcohols.
[0037] Further, in the present invention, the aromatic diol is a fluorodiol represented by the following general formula (1): It is also preferred that the copolymer contains an olefin-based diol.
[0038] [ka]
[0039] In formula (1), R 1 is an alkylene group having 1 to 5 carbon atoms, for example, a methylene group, an ethylene group, Examples of the aryl group include ethylene, propylene, butylene, and pentylene. 2 , R 3 , R 4 and R 5 is a hydrogen atom, an alkyl group having 1 to 5 carbon atoms, an aryl group, or an aralkyl group, They may be the same or different from each other.
[0040] Examples of the alkyl group having 1 to 5 carbon atoms include a methyl group, an ethyl group, a propyl group, and an isopropyl group. Propyl group, butyl group, isobutyl group, pentyl group, neopentyl group, isopentyl group, etc. The aryl group includes an aryl group having 6 to 10 carbon atoms, for example, Examples of the aralkyl group include a phenyl group, a tolyl group, and an o-xylyl group. 7 to 20 aralkyl groups, such as benzyl and phenethyl groups. .
[0041] In the fluorene-based diol represented by the above general formula (1), R 1 As the R can be a methylene group or an ethylene group. 2 , R 3 , R 4 and R 5 As for that, Preferable examples of each of these groups include a hydrogen atom, a methyl group, and an ethyl group, and a hydrogen atom is particularly preferable. As the fluorene-based compound, bisphenoxy is preferred from the viewpoint of availability. Ethanol fluorene, bis(4-(2-hydroxyethoxy)phenyl)fluorene The fluorene-based compounds can be used singly or in combination of two or more. These dihydric alcohols may be used alone or in combination of two or more kinds.
[0042] In the present invention, among the polyhydric alcohols (a2), those that exhibit a high refractive index are In view of the above, it is preferable that the copolymer contains an aromatic diol. It is preferable that the compound contains an aromatic ring. In particular, the compound contains the above-mentioned aromatic ring in order to increase the refractive index while maintaining the adhesiveness. It is preferred that the composition contains a fluorene-based diol.
[0043] The content of aromatic diol in polyhydric alcohol (a2) is ) is preferably 0 to 90 mol %, more preferably 5 to 75 mol %, and even more preferably 1 The content is preferably 0 to 60 mol %, particularly preferably 15 to 40 mol %. If the content is too low, the adhesive performance tends to decrease. It tends to be difficult to obtain a rate.
[0044] The content of the aromatic diol is 10% by weight or more based on the total weight of the polyester resin. It is more preferable that the content is 15 to 85% by weight, particularly 20 to 65% by weight, and especially 25 If the content is too low, a sufficient refractive index cannot be obtained. If the content is too high, the adhesive performance tends to decrease. be.
[0045] Furthermore, the content of the fluorene-based diol is 1:1 based on the total amount of the polyhydric alcohol (a2). It is preferably 0 to 90 mol %, particularly 15 to 80 mol %, and further preferably 20 to 70 mol %. %, and particularly preferably 25 to 60 mol %. If the content is too low, If the refractive index is too high, it tends to be difficult to obtain a desired refractive index, and if the refractive index is too high, the adhesive performance tends to decrease.
[0046] In addition, the content ratio of the fluorene-based diol to the total aromatic diol is sufficient to obtain a sufficient refractive index. From the viewpoint of obtaining the above, 50 mol % or more, particularly 60 mol % or more, further 70 mol % or more, particularly It is preferable that the total amount of the fluorene diol is 90 mol % or more. is particularly preferred.
[0047] Furthermore, in the present invention, among the polyhydric alcohols (a2), the following is preferred in terms of excellent reactivity: It is preferable that the diol contains an aliphatic diol or an alicyclic diol, and particularly preferable that the diol contains an aliphatic diol. Examples of the alcohol include ethylene glycol, 1,3-propanediol, and 2-methyl-1 ,3-Propanediol, Neopentyl glycol, 1,4-Butanediol, 1,5- pentanediol, 1,6-hexanediol, and alicyclic diols such as , 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4 -Cyclohexanedimethanol. Balances flexibility and provides adhesive performance. From this viewpoint, it is particularly preferable that the composition contains an aliphatic diol.
[0048] The content of the aliphatic diol is 1 to 100 mol relative to the total polyhydric alcohol (a2). %, particularly 10 to 85 mol %, further 20 to 80 mol %, and especially 5 The content is preferably 0 to 75 mol %. If the content is too low, the adhesive performance is reduced. If the content is too high, the refractive index tends to decrease.
[0049] In addition, in order to increase the branching points in the polyester resin (A), a polyhydric alcohol having a valence of three or more is used. Examples of the trihydric or higher polyhydric alcohol include pentaerythritol, , dipentaerythritol, tripentaerythritol, glycerin, trimethylol Propane, trimethylolethane, 1,3,6-hexanetriol, adamantanetriol Examples include oars.
[0050] The content of the trihydric or higher polyhydric alcohol in the entire polyhydric alcohol (a2) is It is preferably 10 mol % or less, and particularly preferably 0.1 to 5 mol %. If the content is too high, the production of the polyester resin (A) tends to become difficult. There is.
[0051] In the present invention, the refractive index is greatly affected by the amount of inorganic filler (B) added. However, it is more preferable that the refractive index of the polyester resin (A) is also high. Of the weights of the polyvalent carboxylic acids (a1) and polyhydric alcohols (a2), 10 to 70 It is preferable that 20 to 60% by weight of the aromatic compound is used. It is preferable that the aromatic content is 30 to 49% by weight.
[0052] The mixing ratio of polyvalent carboxylic acids (a1) and polyhydric alcohols (a2) is as follows: It is preferable that the amount of the polyhydric alcohol (a2) is 1 to 2.5 equivalents per equivalent of the polyhydric acid (a1). The amount of the polyhydric alcohol (a2) is preferably 1.1 to 2 equivalents, and particularly preferably 1.1 to 2 equivalents. If the acid value is too high, it tends to be difficult to increase the molecular weight, and if the acid value is too high, the yield decreases. There is a tendency for
[0053] The polyester resin (A) used in the present invention is a polycarboxylic acid (a1) and a polycarboxylic acid (a2). The hydric alcohol (a2) is arbitrarily selected, and is subjected to a polycondensation reaction in the presence of a catalyst by a known method. It is produced by In the polycondensation reaction, an esterification reaction is carried out first, and then a condensation reaction is carried out.
[0054] In such an esterification reaction, a catalyst is used. Specifically, for example, tetraisopropanol is used. Titanium catalysts such as propyl titanate and tetrabutyl titanate, antimony trioxide, etc. Catalysts such as antimony catalysts, germanium catalysts such as germanium dioxide, zinc acetate, Examples of catalysts include manganese acetate and dibutyltin oxide. Among these, the following is preferred because of its balance of high catalytic activity and color: Antimony trioxide, tetrabutyl titanate, germanium dioxide, zinc acetate are preferred. For optical applications, it is preferable to use germanium dioxide.
[0055] The amount of the catalyst to be added is preferably 1 to 10,000 ppm based on the total copolymerization components. It is particularly preferably 10 to 5,000 ppm, and further preferably 20 to 3,000 ppm. If the blending amount is too small, the polymerization reaction tends not to proceed sufficiently. However, this method does not offer any advantage such as shortening the reaction time, and side reactions tend to occur easily.
[0056] The reaction temperature during the esterification reaction is preferably 160 to 280° C., and particularly preferably The reaction temperature is preferably 180 to 250° C., more preferably 200 to 240° C. If the reaction temperature is too low, If the temperature is too high, the reaction will not proceed sufficiently, and if the temperature is too high, side reactions such as decomposition will occur. In addition, the reaction is usually carried out under normal pressure.
[0057] After the esterification reaction, a condensation reaction is carried out. The reaction conditions for the polycondensation reaction are as follows: the same catalyst as that used in the above esterification reaction is used; The reaction temperature is preferably 220 to 280°C, particularly preferably 230 The reaction temperature is set at ~270°C, and the reaction system is gradually reduced in pressure until it is finally reacted at 5hPa or less. preferable. If the reaction temperature is too low, the reaction will not proceed sufficiently, whereas if the reaction temperature is too high, decomposition or the like may occur. There is a tendency for side reactions to occur.
[0058] Thus, the polyester resin (A) used in the present invention is obtained. The glass transition temperature of the polyester resin (A) is determined by the balance between the adhesive properties and, for example, the refractive index. Considering the lance, it is preferable that the temperature is 40° C. or less, particularly 25° C. or less, and further preferably 10° C. or less. It is preferable that the glass transition temperature is 0° C. or lower, and particularly 0° C. or lower. If the glass transition temperature is too high, the flexibility is poor. The adhesive strength is lost, the initial adhesiveness decreases, and it becomes difficult to exert sufficient adhesive strength even with finger pressure. There is a tendency for productivity to decline.
[0059] In addition, plasticizers may be added to increase adhesive strength, but adhesives without plasticizers can also be used. In terms of increasing the strength, it tends to be better to slightly lower the glass transition temperature of the polyester resin. In this case, the glass transition temperature is preferably in the range of -70 to 0°C, and more preferably - The temperature is preferably 50 to -10°C, and more preferably -40 to -20°C. The lower limit of the glass transition temperature is usually −80° C., preferably −50° C., and more preferably The temperature is usually -40°C.
[0060] The glass transition temperature (Tg) of the polyester resin (A) is measured by TA Instruments. The values are measured using a differential scanning calorimeter DSC Q20 manufactured by Menthon. The measurement temperature range was from -90°C to 100°C, and the temperature increase rate was 10°C / min.
[0061] The weight average molecular weight of the polyester resin (A) is set to 8 or less from the viewpoint of the cohesive strength of the adhesive. It is preferably 1,000 to 200,000, and particularly preferably 10,000 to 180,000. More preferably, the weight average molecular weight is 20,000 to 150,000. If the particle size is too small, the adhesive will not have sufficient cohesive strength, and the heat resistance and mechanical strength will tend to decrease. If it is too large, it will lose flexibility and initial adhesion will decrease, and pressure equivalent to finger pressure will be sufficient. It tends to be difficult to exert sufficient adhesive strength.
[0062] The weight average molecular weight above is based on the standard polystyrene molecular weight. The high performance liquid chromatography (Tosoh Corporation, "HLC-8320GPC") was used. Column: TSKgel SuperMultipore HZ-M (Exclusion limit: 2× 10 6 Theoretical plate number: 16,000 plates / unit; Packing material: styrene-divinylbenzene copolymer The measurement is performed using two serially connected tubes (coalescence, filler particle size: 4 μm).
[0063] In the present invention, the refractive index of the polyester resin (A) alone is 1.50. It is preferable that the ratio is 1.530 or more, and particularly preferable that the ratio is 1.530 or more.
[0064] Furthermore, the acid value of the polyester resin (A) is preferably 10 mgKOH / g or less. In particular, it is 3 mgKOH / g or less, further 1 mgKOH / g or less, and especially 0.5 mgKOH / g or less. If the acid value is too high, the polyester-based pressure-sensitive adhesive composition of the present invention may be deteriorated. There is a concern that if a metal layer is placed on one side of the adhesive layer obtained from the composition, it may corrode. For example, when a metal oxide thin film layer is used, corrosion occurs and the metal oxide film In addition, the conductivity of the polymer tends to decrease. The lower the acid value of the polyester resin (A), the more preferable.
[0065] The acid value of the polyester resin (A) is determined based on the neutralization droplet size according to JIS K 0070. This is required by law.
[0066] In the present invention, among the polyester resins (A), those having an acid value of 3 mgK The polyester resin must be less than OH / g, and the polyester must contain ionic groups. It is important that the resin is at least one of the following: It is preferable that the resin is a polyester resin having a viscosity of not more than H / g and containing an ionic group.
[0067] It is important that the acid value of the polyester resin (A) is 3 mgKOH / g or less. It is preferably 1 mgKOH / g or less, and particularly preferably 0.5 mgKOH / g or less. The acid value is 3mgKOH / g or less, so that metal layers will not corrode when they are applied. There is no concern that the coating liquid may become smeared, and the compatibility with the inorganic filler (B) described below is good. The composition has excellent stability, transparency, and coatability.
[0068] Methods for lowering the acid value of the polyester resin (A) include, for example, (1) (2) A method of reducing the acid value in the tertiary process to 10 mgKOH / g or less, and (3) a method of reducing the heat during the polycondensation reaction. (3) Add a hydrolysis inhibitor (described later) and heat at room temperature or higher. Among them, the method (1) is preferred because the production process is simple. Method (3) is preferable because it can reliably reduce the acid value. preferable.
[0069] The polyester resin (A) is a copolymer obtained by polymerization using a copolymer component containing an ionic group. The ionic group can be, for example, a sulfonic acid group. It is obtained by polymerization using a copolymerization component containing an ionic group. From the viewpoint of compatibility with the filler (B), the ionic group is preferably a sulfonate group, specifically For example, as described above, it is preferable to carry out polymerization using a sulfonate group-containing dicarboxylic acid. It is nice.
[0070] Next, the pressure-sensitive adhesive composition of the present invention is preferably made of the polyester resin (A), particularly a polyester resin having an acid value of 3m A polyester resin containing ionic groups and gKOH / g or less is used, and inorganic fillers are used. (B) is contained.
[0071] <Inorganic filler (B)> In the present invention, the inorganic filler is blended to impart various functionalities, For example, it can be effectively used to improve the refractive index, thermal conductivity, electrical conductivity, etc. By blending inorganic filler (B), the adhesive strength of polyester adhesive is improved. It is possible.
[0072] By including the inorganic filler (B), functionality can be imparted to the pressure-sensitive adhesive layer. For example, the refractive index can be increased, and the refractive index of the pressure-sensitive adhesive layer is preferably 1.530 or more. More preferably, it is 1.560 or more, even more preferably, it is 1.600 or more, and particularly preferably The upper limit is usually 1.700, preferably 1.680, and more preferably 1.620. Preferably it is 1.660.
[0073] In the present invention, the inorganic filler (B) may be, for example, an inorganic oxide or an inorganic hydroxide. Among them, inorganic oxides are particularly preferred for producing a coating film with high transparency. I wish.
[0074] The inorganic oxide is not particularly limited, but may be a metal oxide or a nonmetal oxide. Among them, a metal oxide and a reactive functional group that modifies the surface of the metal oxide are preferable. Particles containing an organic substance having a group, more specifically, particles of a metal oxide and a surface of the particles The coated particles (hereinafter, reactive modified metal oxide) are those containing an organic substance having a reactive functional group. The reactive functional group has an interaction with the metal oxide, such as a hydrogen bond, and It can be in a state where it is in contact with another substance, or it can be in a state where it is not in such a state and can interact with another substance. The inorganic oxide is preferably inorganic oxide fine particles in a fine particle state, Further, the inorganic oxide fine particles may be in the form of, for example, fine particle powder, paste or sol. Among them, a sol is preferable.
[0075] As the metal oxide, a metal oxide that is generally used as a filler in a resin is preferred. Examples of such metal oxides include zirconium oxide (ZrO 2 : Zirconia), titanium oxide (TiO 2 : Titania), aluminum oxide (Al 2 O 3 :a Lumina), Iron oxide (Fe 2 O 3 , Fe 3 O 4 ), copper oxide (CuO), zinc oxide (ZnO) , yttrium oxide (Y 2 O 3 : yttria), niobium oxide (Nb 2 O 5 ), Molyb oxide Den (MoO 3 , MoO 2 ), indium oxide (In 2 O 3 ), tin oxide (SnO 2 ), Tantalum oxide (Ta 2 O 5 , TaO 2 ), tungsten oxide (WO 3 , WO 2 ), lead oxide (PbO), Bismuth oxide (Bi 2 O 3 ), cerium oxide (CeO 2 Ceria, alumina oxide Ntimon (Sb 2 O 3 , Sb 2 O 5 ), tin-doped indium oxide (ITO), antimony Doped tin oxide (ATO), fluorine doped tin oxide (FTO), phosphorus doped tin oxide (PTO) , zinc antimonate (AZO), indium-doped zinc oxide (IZO), aluminum doped zinc oxide doped with gallium, zinc oxide doped with gallium, etc.
[0076] The non-metallic oxide is generally silicon oxide, which is used as a filler in resins. Element (SiO 2 : Silica), or boron oxide (B 2 O 3 ) etc.
[0077] These metal oxides and nonmetal oxides may be used alone or in combination. Among these, zirconium oxide (ZrO 2 : Zirconia) and titanium oxide (TiO 2 : titania) is preferred.
[0078] Examples of the reactive functional group in the organic substance having the reactive functional group include hydroxyl, groups, phosphate groups, carboxy groups, amino groups, alkoxy groups, isocyanate groups, acid halides , acid anhydrides, glycidyl groups, chlorosilane groups, and alkoxysilane groups. Organic substances having reactive functional groups, particularly organic substances having isocyanate groups, are highly reactive with metal oxides. This is preferable in that it can improve the stability of the object and the surrounding substances.
[0079] Examples of organic substances having an isocyanate group include acryloxymethyl isocyanate. acrylate, methacryloxymethyl isocyanate, acryloxyethyl isocyanate, Acryloxyethyl isocyanate, acryloxypropyl isocyanate, methacrylo Xypropyl isocyanate, 1,1-bis(acryloxymethyl)ethyl isocyanate Examples include:
[0080] In the reactive modified metal oxide particles, the content of the organic substance having a reactive functional group is The amount is preferably 1 to 40 parts by weight per 100 parts by weight of the oxide.
[0081] The reactive modified metal oxide particles are particles of metal oxides, organic substances having reactive functional groups, organic The solvent and any additives that may be added as necessary are mixed, and the resulting mixture is then mixed with the necessary Depending on the type, ultrasonic treatment or other treatment may be performed to obtain a suspension in which the particles are dispersed in the organic solvent. can be obtained.
[0082] Examples of organic solvents include methyl ethyl ketone, methyl isobutyl ketone, acetone, etc. Ketones such as cyclohexanone, benzene, toluene, xylene, ethylbenzene Aromatic hydrocarbons such as methanol, ethanol, isopropyl alcohol, n-butanol Alcohols such as ethanol, isobutanol, ethylene glycol monomethyl ether, Ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene ethylene glycol monomethyl ether, diethylene glycol monoethyl ether, etc. esters, ethyl acetate, butyl acetate, ethyl lactate, γ-butyrolactone, propylene glycol propylene glycol monoethyl ether acetate Esters such as dimethylformamide, N,N-dimethylacetoacetamide, N As the organic solvent, one of these is preferably used. These may be used alone or in combination of two or more. Optional additives that may be added to the mixture: Examples of the metal chelating agent include metal chelating agents.
[0083] When the reactive modified metal oxide particles are obtained as a suspension in which the particles are dispersed in an organic solvent, the solvent The conditions such as the amount of the solvent are adjusted so that the suspension contains 1 to 80% by weight of reactive modified metal oxide particles. % and then subjecting the resultant to the production of the adhesive composition as is, which is convenient for the production. This is preferable from the standpoint of sex, etc.
[0084] When preparing the mixture, it is preferable to mix the components using a bead mill or the like. By such mixing, secondary particles or higher particles are pulverized to the primary particle level, and the primary particles are The surface can be treated in this state, resulting in a uniform surface treatment.
[0085] The mixture can be further subjected to ultrasonic treatment if necessary. This can be done using a cleaning machine, ultrasonic homogenizer, ultrasonic disperser, or other device. Therefore, a better suspension can be obtained.
[0086] As the reactive modified metal oxide particles, commercially available particles may be used as they are. The particles may be provided as a slurry containing components such as a solvent and additives. The components may be used as they are in the form of a slurry as a material for the pressure-sensitive adhesive composition of the present invention. Metal oxide: ZrO 2 Examples of slurries of reactive modified metal oxide particles containing, e.g. For example, the product name "NANON5 ZR-010" (manufactured by Solar Corporation, solvent: methyl ethyl Ketone, particle content 30%, organic matter with reactive functional groups to modify the surface: polymerizable functional group Examples of the functional group-containing isocyanate include metal oxide. TiO as a compound 2 Examples of slurries of reactive modified metal oxide particles including, for example, Product name: NOD-742GTF (manufactured by Nagase ChemteX Corporation, solvent: polyethylene glycol monomethyl ether, particle content 30%, volume average particle size 48 nm) It is possible.
[0087] The volume average particle size of the inorganic oxide is preferably 5 nm or more, more preferably 1 0 nm or more, particularly preferably 20 nm or more, while preferably 50 nm or less. More preferably, the particle size is 40 nm or less, and particularly preferably, the particle size is 30 nm or less. By setting the value within the above range, a pressure-sensitive adhesive layer with little coloring and high light transmittance can be obtained. In addition, the particles are easily dispersed. The reactive modified metal oxide does not aggregate to form secondary particles or larger particles. When the higher-order particles are constituted, the particle size range may be the primary particle size range.
[0088] The particle size was measured using a dynamic light scattering particle size distribution analyzer (Nanortrac, manufactured by Nikkiso Co., Ltd.). Using a 1000-millimeter wave-exchanger (Wave-EX150), the volume can be measured based on the particle size. Cut.
[0089] In the present invention, the inorganic filler (B) may be a filler having thermal conductivity or a filler having electrical conductivity. Also included are fillers having the following structure. Examples of the thermally conductive filler include silica, alumina, magnesium oxide, and zinc oxide. etc.
[0090] As the conductive filler, for example, lanthanum titanate (LaTiO 3 ), Sulfur oxide (SnO 2 ), zinc oxide (ZnO), indium zinc oxide (In 2 O 3 -ZnO), Antimony tin oxide (SbSnO 2 ), indium oxide (In 2 O 3 ), zinc tin Indium oxide ((Zn,Sn)In 2 O 3 ), Alumina-Zinc Oxide (ZnO-A l 2 O 3 ), Gallium-Zinc Oxide (ZnO-Ga 2 O 3 ) etc.
[0091] In addition to the above, the inorganic filler (B) may also be a metal hydroxide (e.g., magnesium hydroxide). Calcium hydroxide, aluminum hydroxide, zirconium hydroxide, ferrous hydroxide, hydroxide copper oxide); silicates (e.g., talc, mica, clay, dolomite, bentonite, quartz , calcium silicate, aluminum silicate, diatomaceous earth, perlite, zeolite, and silver The constituent elements may be copper, zinc, manganese, etc., and the amino compound is supported on the catalyst. may be used); carbonates (e.g., calcium carbonate, magnesium carbonate); metal salts (e.g., ba light, fluorite, calcium sulfate, aluminum sulfate; metal sulfides (e.g. molybdisulfide dendrimer; metal powders (e.g. aluminum powder, copper powder); inorganic phosphates (e.g. tripolyphosphate aluminum phosphate, zirconium phosphate, titanium phosphate, tin phosphate, etc. From the viewpoints of mechanical properties, dispersibility, and moldability, the volume average particle size is preferably 0.01 to 1.005. The thickness is preferably 30 μm, more preferably 0.5 to 15 μm, and particularly preferably 1 to 10 μm.
[0092] In the present invention, the content of the inorganic filler (B) is 100% by weight of the polyester resin (A). The amount is preferably 10 to 1000 parts by weight, particularly preferably 40 to 500 parts by weight. The content of the inorganic oxide (B) is preferably 90 to 300 parts by weight. If there is too little, the desired refractive index and other functions tend not to be obtained, and if there is too much, the adhesive strength decreases. There is a tendency for
[0093] The polyester-based pressure-sensitive adhesive composition of the present invention comprises the polyester-based resin (A) and an inorganic It contains a filler (B), and also contains a hydrolysis inhibitor (C) and It is preferable that the composition further contains a plasticizer ( It is preferred that the copolymer comprises at least one of the following:
[0094] <Hydrolysis inhibitor (C)> The hydrolysis inhibitor (C) is contained to ensure long-term durability. The hydrolysis inhibitor (C) is not particularly limited, and any of the conventionally known inhibitors may be used. For example, a carboxylic acid terminal group of the polyester resin (A) can be reacted with Specific examples of the compounds include compounds that bond to the carboxyl group through a carbodiimide group, an epoxy group, Among these, compounds having functional groups such as carbodiimide and oxazoline groups are also included. The amido group-containing compound has the effect of eliminating the catalytic activity of the protons derived from the carboxyl end group. Highly preferred.
[0095] The carbodiimide group-containing compound is usually a carbodiimide group (-N=C=N- ) in the molecule, but it is preferable to use a polycarbodiimide having a higher temperature and humidity. In order to improve durability under high temperatures, it is preferable that the compound contains two or more carbodiimide groups in the molecule. It is preferable that the number of the aryl groups is 3 or more, more preferably 5 or more, and even more preferably 7 or more. It is preferable that the number of the groups is more than 30, because the molecular structure becomes too large. In addition, the decarboxylation of diisocyanates in the presence of a carbodiimide catalyst tends to be unsatisfactory. It is also preferable to use a high molecular weight polycarbodiimide produced by a condensation reaction. stomach.
[0096] As such a high molecular weight polycarbodiimide, the following diisocyanates are used: Examples of such compounds include those obtained by polymerization reaction.
[0097] Such diisocyanates include, for example, 4,4'-diphenylmethane diisocyanate. , 3,3'-dimethoxy-4,4'-diphenylmethane diisocyanate, 3,3' -Dimethyl-4,4'-diphenylmethane diisocyanate, 4,4'-diphenyl Diisocyanate, 3,3'-dimethyl-4,4'-diphenyl ether diisocyanate 2,4-tolylene diisocyanate, 2,6-tolylene diisocyanate, 1- Methoxyphenyl-2,4-diisocyanate, isophorone diisocyanate, 4,4' -Dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate These can be used alone or in combination of two or more. The high molecular weight polycarbodiimide may be synthesized or a commercially available product may be used.
[0098] Commercially available carbodiimide group-containing compounds include, for example, Among them, Carbodilite (registered trademark) series is (Registered trademark) V-01, V-03, V-05, V-07, V-09, and V-09GB are organic solvents. It is preferred because it has excellent compatibility with
[0099] Examples of the epoxy compound include glycidyl ester compounds and glycidyl ether compounds. Compounds such as aryl compounds are preferred.
[0100] Specific examples of the glycidyl ester compound include benzoic acid glycidyl ester, t-Bu-benzoic acid glycidyl ester, p-toluic acid glycidyl ester, cyclohexyl Xanthate glycidyl ester, pelargonic acid glycidyl ester, stearic acid Glycyl esters, glycidyl laurate, glycidyl palmitate, Behenic acid glycidyl ester, versatic acid glycidyl ester, oleic acid glycidyl ester glycidyl ester of linoleic acid, glycidyl ester of linoleic acid, behenyl ester Glycidyl ester of glycidyl ester of stearolic acid, diglycidyl ester of terephthalic acid Diglycidyl ester, isophthalic acid diglycidyl ester, phthalic acid diglycidyl ester, sodium Phthalenedicarboxylic acid diglycidyl ester, methyl terephthalic acid diglycidyl ester , Hexahydrophthalic acid diglycidyl ester, Tetrahydrophthalic acid diglycidyl ester ter, cyclohexanedicarboxylic acid diglycidyl ester, adipate diglycidyl ester ter, succinic acid diglycidyl ester, sebacic acid diglycidyl ester, dodecane diamine Diglycidyl ester of octadecanedicarboxylic acid, diglycidyl ester of trimellitic acid triglycidyl ester of pyromellitic acid, tetraglycidyl ester of pyromellitic acid, etc. These can be used alone or in combination of two or more kinds.
[0101] Specific examples of the glycidyl ether compound include phenyl glycidyl ether, o-Phenyl glycidyl ether, 1,4-bis(β,γ-epoxypropoxy)butane , 1,6-bis(β,γ-epoxypropoxy)hexane, 1,4-bis(β,γ-epoxy 1-(β,γ-epoxypropoxy)benzene, 1-(β,γ-epoxypropoxy)-2-ethoxyethane, 1-(β,γ-epoxypropoxy)-2-benzyloxyethane, 2,2-bis-[р -(β,γ-epoxypropoxy)phenyl]propane and 2,2-bis-(4-hydroxyphenyl)propane Bis(4-hydroxyphenyl)propane and 2,2-bis(4-hydroxyphenyl)methane Bisglycidyl polyether obtained by the reaction of sphenol with epichlorohydrin These can be used alone or in combination of two or more.
[0102] The oxazoline compound is preferably a bisoxazoline compound. For example, 2,2'-bis(2-oxazoline), 2,2'-bis(4-methyl-2- oxazoline), 2,2'-bis(4,4-dimethyl-2-oxazoline), 2,2'- Bis(4-ethyl-2-oxazoline), 2,2'-bis(4,4'-diethyl-2-oxazoline) 2,2'-bis(4-propyl-2-oxazoline), 2,2'-bis( 4-butyl-2-oxazoline), 2,2'-bis(4-hexyl-2-oxazoline) , 2,2'-bis(4-phenyl-2-oxazoline), 2,2'-bis(4-cyclohexane 2,2'-bis(4-benzyl-2-oxazoline), 2,2'-bis(4-benzyl-2-oxazoline), 2 ,2'-p-phenylenebis(2-oxazoline), 2,2'-m-phenylenebis(2 -oxazoline), 2,2'-o-phenylenebis(2-oxazoline), 2,2'-p -Phenylenebis(4-methyl-2-oxazoline), 2,2'-p-phenylenebis( 4,4-Dimethyl-2-oxazoline), 2,2'-m-phenylenebis(4-methyl- 2-Oxazoline), 2,2'-m-phenylenebis(4,4-dimethyl-2-oxazoline) phosphorus), 2,2'-ethylenebis(2-oxazoline), 2,2'-tetramethylenebis (2-oxazoline), 2,2'-hexamethylenebis(2-oxazoline), 2,2' -Octamethylenebis(2-oxazoline), 2,2'-decamethylenebis(2-oxa 2,2'-ethylenebis(4-methyl-2-oxazoline), 2,2'-tetramethyl- Lamethylenebis(4,4-dimethyl-2-oxazoline), 2,2'-9,9'-diphenyl 2,2'-cyclohexylenebis(2-oxazoline) 2,2'-diphenylenebis(2-oxazoline), and the like can be exemplified. Among these, 2,2'-bis(2-oxazoline) is the most popular from the viewpoint of reactivity with polyesters. From this viewpoint, it is most preferable. These may be used alone or in combination of two or more kinds.
[0103] It is preferable that the hydrolysis inhibitor (C) has low volatility. It is preferable to use a copolymer having a high molecular weight. Generally, the molecular weight is 300 to 10,000, preferably 1, Use one that is between 000 and 5,000.
[0104] Among the hydrolysis inhibitors (C), it is preferable to use a carbodiimide group-containing compound. In this case, the carbodiimide equivalent is preferably 50 to 10,000, particularly preferably 100 to It is preferable that the carbodiimide equivalent is 1000, and more preferably 150 to 500. indicates the formula weight per carbodiimide group.
[0105] The content of the hydrolysis inhibitor (C) is 100 parts by weight of the polyester resin (A). It is preferably 0.01 to 10 parts by weight, and particularly preferably 0.1 to 5 parts by weight. If the content is too high, the polyester resin may become unstable. It tends to become cloudy due to poor compatibility with fat (A), and if it is too little, it may not have sufficient durability. It tends to be hard to obtain.
[0106] The content of the hydrolysis inhibitor (C) is determined based on the acid value of the polyester resin (A). It is preferable to optimize the content accordingly, and the polyester resin ( The ratio of the amount of functional groups of the hydrolysis inhibitor (C) in the pressure-sensitive adhesive composition to the total acid value (a) of A) The molar ratio ((c) / (a)) of the total (c) is preferably 0.5≦(c) / (a). It is particularly preferable that (c) / (a) is 1≦(c) / (a)≦1,000, and it is further preferable that (c) / (a) is 1.5≦(c) / (a)≦1,000. (a)≦100. If the content ratio of (c) to (a) is too high, the polyester-based The compatibility with resin (A) tends to decrease, and the adhesive strength, cohesive strength, and durability tend to decrease. If the content ratio of (c) to (a) is too low, the moisture and heat resistance tends to decrease.
[0107] <Crosslinking agent (D)> The polyester-based pressure-sensitive adhesive composition of the present invention usually contains a crosslinking agent (D). Preferably, the crosslinking agent (D) is contained in the polyester resin (A) to crosslink the polyester resin (A). D) crosslinking gives it excellent cohesive strength, improving its performance as an adhesive.
[0108] Examples of such a crosslinking agent (D) include polyisocyanate-based compounds, polyepoxy-based Compounds such as hydroxyl groups and / or carboxyl groups contained in the polyester resin (A) Among these, the initial adhesion and mechanical strength are excellent, and In particular, polyisocyanate compounds are used because they can provide a good balance between heat resistance and heat resistance. is preferred.
[0109] Examples of such polyisocyanate compounds include tetramethylene diisocyanate. Hexamethylene diisocyanate, isophorone diisocyanate, tolylene diisocyanate Anate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate xylylene diisocyanate, hydrogenated xylylene diisocyanate, tetramethyl xylylene diisocyanate Silylene diisocyanate, 1,5-naphthalene diisocyanate, triphenylmethane triisocyanate, and other polyisocyanates. Adducts of these polyisocyanates and polyol compounds such as trimethylolpropane, Examples of the isocyanate compound include biuret and isocyanurate. Polyisocyanate compounds are compounds in which the isocyanate moiety is brominated with phenols, lactams, etc. These crosslinking agents (D) may be used alone. Alternatively, two or more of them may be used in combination.
[0110] The content of the crosslinking agent (D) depends on the molecular weight of the polyester resin (A) and the intended use. Although it can be appropriately selected, it is usually the hydroxyl group and / or the hydroxyl group contained in the polyester resin (A). The reactive group contained in the crosslinking agent (D) is 0.2 to 10 equivalents per equivalent of the carboxy group. It is preferable to contain the crosslinking agent (D) in a ratio of 0.5 to 5 equivalents, particularly preferably 0.5 to 5 equivalents. More preferably, the amount is 0.5 to 3 equivalents.
[0111] If the equivalent number of the reactive group contained in the crosslinking agent (D) is too small, the cohesive strength decreases and If the thickness is too large, the flexibility will decrease, the initial adhesion will decrease, and There is a tendency for sufficient adhesive strength to not be achieved with pressure equivalent to that applied with finger pressure.
[0112] When the crosslinking agent (D) is blended, it is preferable to simultaneously contain a catalyst. Such catalysts include metal catalysts such as tin, lead, and bismuth compounds, or iron and copper. transition metal compounds such as titanium, zirconium, nickel, cobalt, and manganese, as well as acetylacetonates. As a non-metallic catalyst, tertiary amine compounds are used. From these, organotin, organotitanium and organozirconium are preferred.
[0113] <Plasticizer (E)> The polyester-based pressure-sensitive adhesive composition of the present invention preferably further contains a plasticizer (E). Such a plasticizer (E) is preferable because it increases the refractive index and causes the glass transition temperature of the resin to rise too high. It is contained to ensure adhesion even when the adhesive is too strong.
[0114] Examples of such plasticizers (E) include alkyl esters of aromatic polycarboxylic acids and , alkyl esters of aliphatic polycarboxylic acids, etc. Alkyl esters of aromatic polycarboxylic acids are preferred because they can exert a plasticizing effect without causing any deterioration. Preferably, the alkyl ester of an aromatic polycarboxylic acid having three or more valences is used.
[0115] The content of the plasticizer (E) is 100 parts by weight of the polyester resin (A). The content is preferably 2 to 30 parts by weight, particularly preferably 3 to 20 parts by weight, and further preferably If the content is too high, the viscosity of the resin may increase due to bleeding out of the plasticizer. If the amount is too small, the adhesive strength will decrease due to poor compatibility. There is.
[0116] Thus, the polyester-based pressure-sensitive adhesive composition of the present invention is obtained. In the present invention, the polyester resin (A), the inorganic filler (B), the hydrolyzed In addition to the inhibitor (C), crosslinking agent (D), and plasticizer (E), any other additives may be used without impairing the effects of the present invention. In the above, conventionally known antioxidants, softeners, ultraviolet absorbers, stabilizers, antistatic agents, tackifiers, etc. Additives such as additives, inorganic or organic fillers, powders such as metal powders, pigments, and particulates Any additives can be added. From the viewpoints of durability and transparency, it is preferable that the tackifier is not substantially contained. preferable.
[0117] The polyester-based pressure-sensitive adhesive of the present invention is made of the above-mentioned polyester-based pressure-sensitive adhesive composition, i.e. That is, it is obtained by curing a polyester-based pressure-sensitive adhesive composition.
[0118] In the polyester-based pressure-sensitive adhesive of the present invention, the adhesive strength (α) of the following polyester-based pressure-sensitive adhesive is , 5N / 25mm or more, preferably 15N / 25mm or more, particularly preferably 20N / 25 If the adhesive strength (α) is smaller than the above range, the adhesiveness tends to be poor. This will result in a decrease in adhesive reliability. The upper limit of adhesive strength (α) is usually 200N / 25 mm, preferably 100N / 25mm, particularly preferably 80N / 25mm.
[0119] Adhesive strength (α): When a polyester adhesive is formed on a substrate to form an adhesive sheet, the adhesive strength After attaching the adhesive to a stainless steel plate and leaving it at 23°C and 50% RH for 30 minutes, 180 degree peel strength (N / 25mm) at a peel speed of 300mm / min.
[0120] The adhesive strength (α) can be measured, for example, as follows.
[0121] That is, the polyester-based pressure-sensitive adhesive composition was applied to a 50 μm-thick polyethylene terephthalate ( PET) film using an applicator, dried at 100°C for 3 minutes, and A polyester-based adhesive composition layer (thickness: 25 μm) was then formed, and the obtained polyester-based adhesive composition layer was then The surface of the composition layer was covered with a release-treated PET film (release film), and the layer was heated at 40° C. for 10 After aging for 10 days, a pressure-sensitive adhesive sheet with a release film was obtained. Peel off the adhesive, roll a 2kg roller twice on a glass plate, and apply to the glass plate. After leaving it at 30% RH for 30 minutes, the 180 degree peel strength (N / 2 The adhesive strength (α) is calculated by measuring the adhesive distance (α = 5 mm).
[0122] In addition, the polyester-based pressure-sensitive adhesive of the present invention has a glass transition temperature that is indicative of the adhesive properties and various functions. From the viewpoint of the balance between the optical properties and the refractive index, the temperature is preferably 30° C. or less, and more preferably 20 It is preferable that the glass transition temperature is not higher than 10° C., more preferably not higher than 0° C. If the strength is too high, the flexibility will be lost and the initial adhesiveness will decrease, and sufficient adhesiveness will not be obtained with finger pressure. The lower limit of the glass transition temperature is usually - The temperature is 80°C, preferably -50°C, and more preferably -40°C.
[0123] Here, the glass transition temperature (Tg) of the polyester-based pressure-sensitive adhesive is It can be determined in the same manner as in the case of resin (A).
[0124] In the present invention, the polyester-based adhesive is substantially free of acidic groups. It is preferable that the acid value is 10 mgKOH / g or less, and more preferable that the acid value is 10 mgKOH / g or less. or 5 mgKOH / g or less, particularly preferably 3 mgKOH / g or less, and further preferably 1 It is preferably 0.5 mgKOH / g or less, and more preferably 0.5 mgKOH / g or less. The acid value of the polyester-based pressure-sensitive adhesive is the same as the acid value of the polyester-based resin (A). It can be found in a variety of ways.
[0125] The polyester-based pressure-sensitive adhesive composition of the present invention can be used for bonding various members. Among these, it is preferable to use it as a pressure-sensitive adhesive for optical members for bonding optical members. The pressure-sensitive adhesive layer of the polyester-based pressure-sensitive adhesive composition is then applied to the optical part. By laminating the adhesive layer on the substrate, the above-mentioned pressure-sensitive adhesive layer-attached optical member can be obtained.
[0126] Such optical members include inorganic and organic conductive films such as ITO electrode films and polythiophene. Transparent electrode films, polarizing plates, retardation plates, elliptical polarizing plates, optical compensation films, brightness enhancement films, Electromagnetic wave shielding film, near infrared absorbing film, AR (anti-reflection) film Among these, it is effective when the optical component is a transparent electrode film, and has high viscosity. The ITO electrode film is particularly preferred because it provides a good adhesion. In most cases, IT is formed as a thin film on a substrate such as glass or PET. It is particularly preferable to use a film in which the O electrode film is formed as a thin film on a PET substrate. In addition, it is used for light extraction films that are provided on the light-emitting surface of surface emitters of organic EL elements, and for liquid crystal displays. It is also suitable as a light diffusion sheet for rays.
[0127] The optical member with the pressure-sensitive adhesive layer further has a release sheet on the surface of the pressure-sensitive adhesive layer opposite to the optical member surface. When the adhesive layer is put into practical use, the release sheet is peeled off, and the adhesive layer is The release sheet is a silicone-based release sheet. is preferred.
[0128] The polyester-based pressure-sensitive adhesive of the present invention may be applied to one or both sides of a support substrate. In particular, it can be used as a pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer comprising the above-mentioned. The adhesive sheet is suitable for use as an optical member adhesive sheet for bonding. It is a substrate-less double-sided PSA sheet that does not have a supporting substrate, because it has high adhesive strength to the surface. is also preferred.
[0129] In the present invention, the term "sheet" includes "film" and "tape." This is what is stated.
[0130] <Adhesive sheet> The pressure-sensitive adhesive sheet can be produced, for example, as follows. The adhesive sheet can be manufactured according to a known method for manufacturing an adhesive sheet. For example, the pressure-sensitive adhesive composition may be applied to a substrate sheet, dried, and then the opposite side of the substrate may be A release sheet is attached to the surface of the pressure-sensitive adhesive layer, and if necessary, cured to form the polyester film of the present invention on the substrate. Thus, the pressure-sensitive adhesive sheet of the present invention having a pressure-sensitive adhesive layer made of a terephthalate is obtained.
[0131] The pressure-sensitive adhesive composition is applied to a release sheet, dried, and a substrate is attached to the opposite side of the pressure-sensitive adhesive layer. The pressure-sensitive adhesive sheet of the present invention can also be obtained by laminating the sheets together and curing them as necessary.
[0132] In addition, a pressure-sensitive adhesive layer is formed on a release sheet, and a release sheet is attached to the opposite side of the pressure-sensitive adhesive layer. This makes it possible to produce a substrate-less double-sided PSA sheet. When using the obtained pressure-sensitive adhesive sheet or substrate-less double-sided pressure-sensitive adhesive sheet, the release sheet is adhered to the sheet. The adhesive layer is peeled off and the adhesive layer is attached to an adherend.
[0133] Examples of the substrate include polyethylene naphthate, polyethylene terephthalate, Polybutyrene terephthalate, polyethylene terephthalate / isophthalate copolymer, etc. Polyester resins such as polyethylene, polypropylene, polymethylpentene, etc. olefin resins; polyvinyl fluoride, polyvinylidene fluoride, polyethylene fluoride, etc. Fluorinated ethylene resin; nylon 6, nylon 6,6 and other polyamides; polyvinyl chloride, Polyvinyl chloride / vinyl acetate copolymer, ethylene-vinyl acetate copolymer, ethylene-vinyl vinyl alcohol copolymers, polyvinyl alcohol, vinylon and other vinyl polymers; triacetic acid cellulosic acid Cellulosic resins such as cellulose and cellophane; polymethyl methacrylate, polymethacrylic acid acrylic resins such as polystyrene, polyethyl acrylate, polybutyl acrylate, etc. Polyimide; Cycloolefin polymer; Polycarbonate; Polyarylate; synthetic resin sheet, aluminum, copper, iron metal foil, fine paper, glassine paper, glass fiber, Examples of the substrate sheets include woven fabrics and nonwoven fabrics made of natural fibers and synthetic fibers. The material can be used as a laminated body or as a multi-layer body in which two or more types are laminated.
[0134] Among these, substrate sheets made of polyethylene terephthalate and polyimide are particularly preferred. It is preferable to use polyethylene terephthalate, since it has excellent adhesion to the adhesive. Furthermore, the base material and the adhesive are polyethylene terephthalate having a metal thin film layer. The adhesive strength of the adhesive is excellent, and the substrate can be stably maintained without corroding the metal thin film layer. This is preferable in that the effect of the polyester-based pressure-sensitive adhesive can be significantly exhibited.
[0135] In the present invention, the ITO electrode film is formed as a thin film on a PET substrate. The PET side of the film has an adhesive layer, and the PET substrate and polycarbonate film are bonded together through the adhesive layer. It is also preferable to form an optical laminate by laminating a glass substrate and an acrylic film thereon. (Layer structure: ITO electrode film / PET substrate / adhesive layer / PC film / acrylic film Hmm). In addition, the refractive index of the base film adjacent to the pressure-sensitive adhesive layer is 1.52 to 1.70. This is preferable in that when it is laminated with the pressure-sensitive adhesive of the present invention, the light extraction property is good.
[0136] Examples of the release sheet include the various synthetic resin sheets, paper, cloth, etc., exemplified above as the base material. Nonwoven fabrics that have been treated for release can be used. As the release sheet, silicone-based It is preferable to use a release sheet such as the above.
[0137] The thickness of the substrate is preferably, for example, 1 to 1000 μm, and particularly preferably The thickness is preferably 2 to 500 μm, and more preferably 3 to 300 μm.
[0138] The pressure-sensitive adhesive composition can be applied by, for example, a gravure roll coater or a reverse roll coater. Roll coater, kiss roll coater, dip roll coater, bar coater, knife coater A coater, spray coater, etc. may be used.
[0139] The conditions for the above curing treatment are usually room temperature to 70°C and the time is usually 1 to 30 days. Specifically, for example, at 23° C. for 1 to 20 days, preferably at 23° C. for 3 to 14 days. This can be done under conditions such as 40°C for 1 to 10 days.
[0140] As for the drying conditions, the drying temperature is preferably 60 to 140°C, and more preferably 80 The drying temperature is preferably 0.5 to 30 minutes, and particularly preferably 2 to 5 minutes. It is.
[0141] The thickness of the pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet or substrate-less double-sided pressure-sensitive adhesive sheet is 2 to 500 μm. It is preferable that the thickness is 5 to 200 μm, particularly preferably 10 to 100 μm. If the thickness of the adhesive layer is too thin, the adhesive strength tends to decrease, whereas if it is too thick, the adhesive layer may not adhere uniformly. This makes it difficult to coat the surface of the material, and also tends to cause problems such as air bubbles in the coating. When considering shock absorption, the thickness is preferably 50 μm or more.
[0142] The thickness of the adhesive layer was measured using a Mitutoyo "ID-C112B" adhesive sheet. By subtracting the thickness measurements of components other than the adhesive layer from the overall thickness measurement, This is the desired value.
[0143] The gel fraction of the adhesive layer of the above-mentioned adhesive sheet should be 20% or less from the viewpoints of durability and adhesive strength. More preferably, the ratio is 30 to 90%, and even more preferably, 40 to 70%. If the gel fraction is too low, the cohesive strength decreases, which tends to decrease durability. If the gel fraction is too high, there is a concern that the adhesive strength will decrease due to an increase in cohesive strength.
[0144] The gel fraction is an index of the degree of crosslinking and is calculated, for example, by the following method. That is, the base polymer sheet (e.g., polyethylene terephthalate film, etc.) The adhesive sheet (without a separator) on which the adhesive layer is formed is 200 mesh. The specimen was wrapped in a stainless steel wire mesh and immersed in toluene at 23°C for 24 hours to remove impurities remaining in the wire mesh. The weight percentage of the dissolved adhesive component is the gel fraction. However, the weight of the substrate is to be subtracted. .
[0145] Furthermore, such a pressure-sensitive adhesive sheet may be provided with a release sheet on the outside of the pressure-sensitive adhesive layer for protection, if necessary. In the case of a pressure-sensitive adhesive sheet in which a pressure-sensitive adhesive layer is formed on one side of a substrate, By subjecting the surface opposite to the adhesive layer of the adhesive sheet to a release treatment, the adhesive layer can be attached to the adhesive sheet by using the release-treated surface. It is also possible to protect the layer. EXAMPLES
[0146] The present invention will be described in more detail below with reference to examples, but the present invention does not exceed the gist of the present invention. The present invention is not limited to the following examples. In the examples, "parts" and "%" refer to weight percent. It means standards.
[0147] In the following examples, the weight average molecular weight and glass transition temperature of the polyester resin are The measurement was performed according to the method described above. Acid value of polyester resin 1 g of polyester resin was dissolved in 3 parts of a mixed solvent (toluene / methanol) (7 / 3 by weight). The solution was dissolved in 0 g of water and measured by neutralization titration based on JIS K 0070.
[0148] <Production of polyester resin (A)> In the following manufacturing examples, the moles are calculated based on the total amount of polycarboxylic acid components taken as 1.0 mole. The molar ratios are shown.
[0149] [Production Example 1: Production of Polyester Resin (A-1)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 40.3 parts (0.95 moles) of sebacic acid, sulfonyl isophthalic acid 3.1 parts (0.05 moles) of sodium dimethyl ester, Pentyl glycol 15.3 parts (0.7 moles), 1,4-butanediol 13.2 parts (0 0.7 moles) and 0.4 parts (0.013 moles) of trimethylolpropane, bisphenoxy Ethanol fluorene 27.6 parts (0.3 moles), tetrabutyl titanate as a catalyst 0.01 parts of ethyl alcohol was added, and the internal temperature was gradually increased to 250°C, followed by esterification reaction for 4 hours. After that, the internal temperature was raised to 260°C, and 0.0% tetrabutyl titanate was added as a catalyst. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to produce polyester. A resin (A-1) was produced. The weight average molecular weight of the resulting polyester resin (A-1) was 46,000, and the glass transition temperature was 100° C. The temperature was -27°C, the acid value was 0.5 mg KOH / g, and the refractive index was 1.537. The final component ratio is sebacic acid / sulfonylurea as polycarboxylic acid components. Sodium sophthalate = 95 mol% / 5 mol%, polyhydric alcohol component is neopen Tetriglyl / 1.4-Butanediol / Trimethylolpropane / Bisphenoxyethyl Tanolfluorene=33.4 mol% / 36.5 mol% / 0.8 mol% / 29.3 mol% It was.
[0150] [Production Example 2: Production of Polyester Resin (A-2)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 14.4 parts (0.3 moles) of adipic acid and 37.2 parts of isophthalic acid (0.68 moles), 1.95 parts (0.02 moles) of sodium dimethyl sulfonyl isophthalate As the polyol component (a2), 13.7 parts (0.4 mol) of neopentyl glycol ), 1,6-hexanediol 21.4 parts (0.55 moles), ethylene glycol 11. 2 parts (0.55 moles), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature The temperature was gradually increased to 250°C, and the esterification reaction was carried out over 4 hours. The temperature was raised to 60°C, 0.01 parts of tetrabutyl titanate was added as a catalyst, and the mixture was stirred for 1.33 hours. The pressure was reduced to 100 Pa, and the polymerization reaction was carried out for 3 hours to produce polyester resin (A-2). Ta. The weight average molecular weight of the resulting polyester resin (A-2) was 22,000, and the glass transition temperature was 100° C. The temperature was -5°C, the acid value was 0.4 mg KOH / g, and the refractive index was 1.530. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. / Sodium dimethyl sulfonyl isophthalate = 30 mol% / 68 mol% / 2 mol%, The hydric alcohol components are ethylene glycol, neopentyl glycol, and 1.6-hexyl glycol. Xanediol=34.7 mol % / 26.2 mol % / 39.2 mol %.
[0151] [Production Example 3: Production of polyester resin (A-3)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 14.4 parts (0.3 moles) of adipic acid and 37.2 parts of isophthalic acid (0.68 moles), 1.95 parts (0.02 moles) of sodium dimethyl sulfonyl isophthalate As the polyol component (a2), 13.7 parts (0.4 mol) of neopentyl glycol ), 1,6-hexanediol 21.4 parts (0.55 moles), ethylene glycol 11. 2 parts (0.55 moles), and 0.01 parts of tetrabutyl titanate as a catalyst were charged, and the internal temperature The temperature was gradually increased to 240°C, and the esterification reaction was carried out over 3 hours. The temperature was raised to 60°C, 0.01 parts of tetrabutyl titanate was added as a catalyst, and the mixture was stirred for 1.33 hours. The pressure was reduced to 100 Pa, and the polymerization reaction was carried out for 3 hours to produce polyester resin (A-3). Ta. The weight average molecular weight of the resulting polyester resin (A-3) was 20,000, and the glass transition temperature was 100° C. The temperature was -5°C, the acid value was 1.2 mg KOH / g, and the refractive index was 1.530. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. / Sodium dimethyl sulfonyl isophthalate = 30 mol% / 68 mol% / 2 mol%, The hydric alcohol components are ethylene glycol, neopentyl glycol, and 1.6-hexyl glycol. Xanediol=34.7 mol % / 26.2 mol % / 39.2 mol %.
[0152] [Production Example 4: Production of polyester resin (A-4)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 14.4 parts (0.3 moles) of adipic acid and 37.2 parts of isophthalic acid (0.68 moles), 1.95 parts (0.02 moles) of sodium dimethyl sulfonyl isophthalate As the polyol component (a2), 13.7 parts (0.4 mol) of neopentyl glycol ), 1,6-hexanediol 21.4 parts (0.55 moles), ethylene glycol 11. 2 parts (0.55 moles), and 0.005 parts of tetrabutyl titanate as a catalyst. The temperature was gradually increased to 230°C, and the esterification reaction was carried out over 2.5 hours. Raise the internal temperature to 260°C, charge 0.01 parts of tetrabutyl titanate as a catalyst, and add 1. The pressure was reduced to 33 hPa, and the polymerization reaction was carried out for 3 hours to obtain polyester resin (A-4). Manufactured. The weight average molecular weight of the resulting polyester resin (A-4) was 15,000, and the glass transition temperature was 1.0° C. The temperature was -6°C, the acid value was 2.6 mg KOH / g, and the refractive index was 1.530. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. / Sodium dimethyl sulfonyl isophthalate = 30 mol% / 68 mol% / 2 mol%, The hydric alcohol components are ethylene glycol, neopentyl glycol, and 1.6-hexyl glycol. Xanediol=34.7 mol % / 26.2 mol % / 39.2 mol %.
[0153] [Production Example 5: Production of polyester resin (A-5)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 14.6 parts (0.3 moles) of adipic acid and 38.6 parts of isophthalic acid (0.70 mol), as polyol component (a2), 13.8 parts of neopentyl glycol (0.4 moles), 1,6-hexanediol 21.6 parts (0.55 moles), ethylene glycol Coal 11.3 parts (0.55 moles), tetrabutyl titanate 0.01 parts as a catalyst After the addition, the internal temperature was gradually increased to 250°C, and the esterification reaction was carried out over 4 hours. After that, the internal temperature is raised to 260°C, and 0.01 parts of tetrabutyl titanate is added as a catalyst. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 3 hours to form a polyester resin (A- 5) was manufactured. The weight average molecular weight of the resulting polyester resin (A-5) was 33,000, and the glass transition temperature was 100° C. The temperature was -5°C, the acid value was 0.5 mg KOH / g, and the refractive index was 1.530. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. = 30 mol% / 70 mol%, polyhydric alcohol component is ethylene glycol / neopentyl butyl glycol / 1,6-hexanediol=34.7 mol% / 26.2 mol% / 39 .2 mol%.
[0154] [Production Example 6: Production of polyester resin (A-6)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 45.9 parts (0.8 moles) of sebacic acid, 7.1 parts ( 0.15 mol), 4.2 parts (0.05 mol) of sodium dimethyl sulfonyl isophthalate 26.6 parts (0.9 moles) of neopentyl glycol as the polyol component (a2), 1,4-butanediol 12.8 parts (0.5 moles), 1,6-hexanediol 2.9 parts (0.087 moles) and 0.5 parts (0.013 moles) of trimethylolpropane, a catalyst and Then, 0.01 parts of tetrabutyl titanate was added and the internal temperature was gradually increased to 250°C. The esterification reaction was carried out for 4 hours. After that, the internal temperature was raised to 260°C, and the catalyst was added. Charge 0.01 parts of tetrabutyl titanate, reduce pressure to 1.33 hPa, and then heat for 3 hours. A polymerization reaction was carried out to produce a polyester resin (A-6). The weight average molecular weight of the resulting polyester resin (A-6) was 51,000, and the glass transition temperature was 100° C. The temperature was -49°C, the acid value was 0.8 mg KOH / g, and the refractive index was 1.489. The final component ratio is sebacic acid / isophthalic acid as polycarboxylic acid components. / Sodium sulfonyl isophthalate = 80 mol% / 15 mol% / 5 mol%, polyhydric alcohol The alcohol components are neopentyl glycol, 1.4-butanediol, and 1.6-hexadecyl glycol. Trimethylolpropane / trimethylolpropane=58.7 mol% / 34.1 mol% / 6.2 mol% / 1.0 mol %.
[0155] [Production Example 7: Production of polyester resin (A-7)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 9.6 parts (0.2 moles) of isophthalic acid and 46.8 parts (0.2 moles) of sebacic acid were used. parts (0.8 moles), and as polyol component (a2), 27.1 parts of neopentyl glycol (0.9 moles), 1,4-butanediol 13.0 parts (0.5 moles), 1,6-hexane 3.0 parts (0.09 moles) of diol and 0.5 parts (0.013 moles) of trimethylolpropane 0.01 parts of tetrabutyl titanate as a catalyst was added, and the internal temperature was gradually increased to 250°C. The temperature was gradually increased and the esterification reaction was carried out over 4 hours. After that, the internal temperature was increased to 260°C. 0.01 parts of tetrabutyl titanate was added as a catalyst, and the pressure was reduced to 1.33 hPa. The polymerization reaction was carried out for 3 hours to produce a polyester resin (A-7). The weight average molecular weight of the resulting polyester resin (A-7) was 70,000, and the glass transition temperature was 100° C. The temperature was -50°C, the acid value was 0.2 mg KOH / g, and the refractive index was 1.486. The final composition is sebacic acid / isophthalic acid = 8 as polycarboxylic acid components. 0 mol% / 20 mol%, and the polyhydric alcohol component is neopentyl glycol / 1.4 -Butanediol / 1.6-Hexanediol / Trimethylolpropane = 58.8 moles % / 34.1 mol % / 6.2 mol % / 1.0 mol %.
[0156] [Production Example 8: Production of polyester resin (A-8)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 14.4 parts (0.3 moles) of adipic acid and 37.2 parts of isophthalic acid (0.68 moles), 1.95 parts (0.02 moles) of sodium dimethyl sulfonyl isophthalate As the polyol component (a2), 13.7 parts (0.4 mol) of neopentyl glycol ), 1,6-hexanediol 21.4 parts (0.55 moles), ethylene glycol 11. 2 parts (0.55 moles), and 0.005 parts of tetrabutyl titanate as a catalyst. The temperature was gradually increased to 220°C, and the esterification reaction was carried out over 2 hours. The temperature was raised to 260°C, 0.01 parts of tetrabutyl titanate was added as a catalyst, and the temperature was adjusted to 1.33 The pressure was reduced to 100 psi and the polymerization reaction was carried out for 3 hours to produce polyester resin (A-8). did. The weight average molecular weight of the resulting polyester resin (A-8) was 19,000, and the glass transition temperature was The temperature was -6°C, the acid value was 5.5 mg KOH / g, and the refractive index was 1.530. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. / Sodium dimethyl sulfonyl isophthalate = 30 mol% / 68 mol% / 2 mol%, The hydric alcohol components are ethylene glycol, neopentyl glycol, and 1.6-hexyl glycol. Xanediol=34.7 mol % / 26.2 mol % / 39.2 mol %.
[0157] [Production Example 9: Production of polyester resin (A-9)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 33.6 parts (0.681 moles) of adipic acid and 16. 9 parts (0.30 moles), 1.9 parts (0.01 9 moles), and as the polyol component (a2), 14.1 parts (0.4 mol), 1,6-hexanediol 22.0 parts (0.55 mol), ethylene glycol 1 1.5 parts (0.55 moles) of tetrabutyl titanate as a catalyst was added. The internal temperature was gradually increased to 220°C, and the esterification reaction was carried out over 2 hours. Raise the internal temperature to 260°C, charge 0.01 parts of tetrabutyl titanate as a catalyst, and add 1. The pressure was reduced to 33 hPa, and the polymerization reaction was carried out for 3 hours to obtain polyester resin (A-9). Manufactured. The weight average molecular weight of the resulting polyester resin (A-9) was 21,000, and the glass transition temperature was 100° C. The temperature was -35°C, the acid value was 0.3 mg KOH / g, and the refractive index was 1.501. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. / Sodium dimethyl sulfonyl isophthalate = 68.1 mol% / 30 mol% / 1.9 mol The polyhydric alcohol components are ethylene glycol / neopentyl glycol / 1 .6-Hexanediol=34.7 mol % / 26.2 mol % / 39.2 mol %.
[0158] [Production Example 10: Production of Polyester Resin (A'-1)] A reaction vessel equipped with a thermometer, stirrer, distillation column, nitrogen inlet tube and vacuum device is filled with polyvalent carboxylic acid. As the acid component (a1), 14.6 parts (0.3 moles) of adipic acid and 38.6 parts of isophthalic acid (0.70 mol), as polyol component (a2), 13.8 parts of neopentyl glycol (0.4 moles), 1,6-hexanediol 21.6 parts (0.55 moles), ethylene glycol Coal 11.3 parts (0.55 moles), tetrabutyl titanate 0.005 parts as a catalyst The internal temperature was gradually increased to 220°C, and the esterification reaction was carried out for 2 hours. After that, the internal temperature was raised to 250°C, and 0.01 parts of tetrabutyl titanate was added as a catalyst. The pressure was reduced to 1.33 hPa, and the polymerization reaction was carried out for 2 hours to form a polyester resin (A '-1) was manufactured. The weight average molecular weight of the resulting polyester resin (A'-1) was 25,000 and the glass transition temperature was 100°C. The transfer temperature was -7°C, the acid value was 5.9 mg KOH / g, and the refractive index was 1.530. The final component ratio is adipic acid / isophthalic acid as polycarboxylic acid components. = 30 mol% / 70 mol%, polyhydric alcohol component is ethylene glycol / neopentyl butyl glycol / 1,6-hexanediol=34.7 mol% / 26.2 mol% / 39 .2 mol%.
[0159] [Production of polyester resin (A'-2)] In a reactor equipped with a thermometer, agitator, a rectification column, and a nitrogen inlet tube, dicarboxylic acids such as sesame, sulphur, and sulphuric acid were added. 49.5 parts (0.9 moles) of basic acid, 4.5 parts (0.1 moles) of isophthalic acid, polyol As a result, 28.3 parts (1 mole) of neopentyl glycol and 6.4 parts (1 mole) of 1,6-hexanediol were used. The mixture was charged with 0.2 moles of tetrabutyl titanate as a catalyst, and the internal temperature was adjusted to 260 The temperature was raised to 260°C over 2 hours, and the esterification reaction was carried out at 260°C for 3 hours. Thereafter, the internal temperature was lowered to 170° C., and 11.3 parts (0.19 moles) of pyromellitic anhydride was added. The chain extension reaction was carried out for 1 hour to produce a polyester resin (A'-2). The polyester resin (A'-2) has a weight average molecular weight of 28,900 and a glass transition temperature The temperature was -32°C and the acid value was 70.1 mg KOH / g. The final component ratio is sebacic acid / isophthalic acid as polycarboxylic acid components. / pyromellitic acid = 75.6 mol% / 8.4 mol% / 16.0 mol%, polyhydric alcohol content The molar ratio was neopentyl glycol / 1.6-hexanediol = 83.3 mol% / 1 It was 6.7 mol%.
[0160] <Inorganic filler (B)> The following inorganic fillers were prepared: (B-1) "AX-ZP-158-A" (manufactured by Nippon Shokubai Co., Ltd., zirconium oxide dispersion liquid) ) (B-2) "NANON5 ZR-010" (manufactured by Solar Co., Ltd., zirconium oxide content) Spray) (B-3) "ZIRCOSTAR ZP-153" (manufactured by Nippon Shokubai Co., Ltd., zirconium oxide (Um dispersion)
[0161] <Hydrolysis inhibitor (C)> The following was prepared as the hydrolysis inhibitor (C). (C-1) Carbodiimide group-containing hydrolysis inhibitor (manufactured by Nisshinbo Chemical Co., Ltd.; trade name "Carbo Zilite V-09GB
[0162] <Crosslinking agent (D)> The following was prepared as the crosslinking agent (D). (D-1) Trimethylolpropane / tolylene diisocyanate adduct (Nippon Polyurethane (manufactured by Epson Corporation; product name: Coronate L55E)
[0163] <Plasticizer> The following plasticizers were prepared: (E-1) Trioctyl trimellitate (TOTM)
[0164] <Catalyst> The following catalysts were prepared: Dibutyltin dilaurate (DBTL) diluted to 1% with acetylacetone.
[0165] <Antioxidants> The following antioxidants were prepared: Hindered phenolic antioxidant / Irganox 1010 (manufactured by BASF)
[0166] [Preparation of polyester resin solution] The polyester resin obtained above was diluted with ethyl acetate to a solid content of 50% to obtain a polyester. A steric resin solution was obtained.
[0167] (Examples 1 to 6, Comparative Examples 1 to 2) 200 parts of the polyester resin solution obtained above (100 parts solids) were mixed at room temperature (2 Mix the ingredients as shown in Table 1 at 0°C to 30°C to obtain a solid content of 25%. The mixture was stirred and mixed to obtain a polyester-based pressure-sensitive adhesive composition solution. The obtained polyester-based pressure-sensitive adhesive composition solution was evaluated as follows. As shown in Table 1.
[0168] [Solution stability] The polyester-based adhesive composition solution obtained above was stirred with a rod for 1 minute, and then left for 5 minutes. The mixture was mixed using a rolling mixer. The solution state was then checked by tilting the container and visually observing the increase in viscosity. The evaluation criteria are as follows: 5. The solution viscosity remains low and the fluidity is high. 4. Although a slight increase in viscosity was observed, the fluidity was high. 3. Slight increase in viscosity observed 2. Less liquidity 1. Liquidity is lost
[0169] [Solution transparency] When checking the solution stability, the transparency of the solution was visually confirmed. The evaluation criteria were as follows: be. ○ The solution was completely transparent or slightly hazy but transparent. △ The solution was slightly milky and cloudy. × The solution was completely cloudy.
[0170] <Manufacturing of adhesive sheets with release films> The polyester-based pressure-sensitive adhesive compositions obtained in Examples 1 to 6 and Comparative Examples 1 and 2 were each Apply with an applicator onto a 0 μm polyethylene terephthalate (PET) film The resulting adhesive composition layer (thickness: 25 μm) was then dried at 100° C. for 3 minutes. The surface of the adhesive composition layer was covered with a release-treated PET film (release film), and the adhesive composition was then heated for 40 C. for 10 days to obtain a pressure-sensitive adhesive sheet with a release film.
[0171] The adhesive sheet with release film was used to measure the gel fraction, adhesive strength, and optical properties as follows. The properties (refractive index, transparency) were evaluated. The results are shown in Table 1.
[0172] [Gel fraction (%)] Peel off the release film from the adhesive sheet with release film obtained above and apply 200 mesh The specimen was wrapped in a stainless steel wire mesh and immersed in toluene at 23°C for 24 hours. The weight percentage of the adhesive component in the solution was calculated as the gel fraction. However, the weight of the substrate was subtracted. Oops.
[0173] [Adhesive strength (N / 25mm)] The release film was peeled off from the pressure-sensitive adhesive sheet with release film obtained above, and the glass plate was Apply the tape to the substrate in an environment of 23℃ 50% RH by rolling it back and forth twice with a 2kg roller for 30 minutes. After that, the 180 degree peel strength (N / 25mm) was measured at a peel speed of 300mm / min. The adhesive strength was measured using an autograph (Shimadzu Corporation's "Autograph"). The adhesive strength was evaluated using the following criteria: (Evaluation Criteria) ○:5N / 25mm or more ×: Less than 5N / 25mm
[0174] [Refractive index] The pressure-sensitive adhesive sheet with release film obtained above was left at 23°C for 3 hours, and the release film was The adhesive layer side was measured with Abbe refraction system DR-M4 manufactured by Atago Co., Ltd. using the D line (58 The refractive index at wavelengths of 100 nm and 9 nm was measured.
[0175] [Transparency] The transparency of the pressure-sensitive adhesive sheet with release film obtained above was visually observed. ○...Transparent △: Slightly cloudy ×: Cloudy
[0176] [Table 1]
[0177] From the above results, it can be seen that in Examples 1 to 6, the adhesive strength is excellent and the refractive index is very high. In contrast, Comparative Examples 1 and 2, which do not contain inorganic filler, have poor adhesion. Furthermore, the refractive index is also relatively low.
[0178] (Examples 7 to 19, Comparative Examples 3 to 7) The polyester resin obtained above was mixed with a 1:1 mixture of methyl ethyl ketone and ethyl acetate. The polyester resin solution was diluted with the mixed solution to a solids concentration of 25%, and 400 parts of the solution (solids concentration 100 (parts) of the mixture, as shown in Table 2, was mixed with inorganic filler (B) and hydrolysis inhibitor (C). The mixture was stirred and mixed to obtain a polyester-based pressure-sensitive adhesive composition solution. The obtained polyester-based pressure-sensitive adhesive composition solution was used to test the solution stability and The refractive index of the solution was measured, and the results are shown in Table 2.
[0179] [Table 2]
[0180] From the above results, it is apparent that the polyester resin having a low acid value, particularly the ion-based resin, is used in Examples 7 to 19. The polyester resins of Examples 7 to 16, which are also carboxylic acid-containing polyester resins, have a high refractive index while , and the solution stability and transparency were excellent. Comparative Example 3, which is not used, has a low refractive index and is made of a polyester resin with a high acid value. In Comparative Examples 4 to 7, the solution stability was poor due to the high acid value, and the solution was not suitable for practical use. It was something I couldn't imagine.
[0181] (Examples 20 to 22) The polyester resin obtained above was mixed with methyl ethyl ketone and ethyl acetate in a ratio of 1:1. The polyester resin solution was diluted with the mixed solution to a solids concentration of 25%, and 400 parts of the solution (solids concentration 100 (parts) of the mixture, as shown in Table 3, was mixed with inorganic filler (B) and hydrolysis inhibitor (C). The mixture was stirred and mixed to obtain a polyester-based pressure-sensitive adhesive composition solution. The obtained polyester-based pressure-sensitive adhesive composition solution was used to test the solution stability and The results are shown in Table 3.
[0182] [Table 3]
[0183] From the above results, it is possible to confirm that the polyester resin containing ionic groups has a high acid value. Examples 20 to 22 are somewhat inferior in terms of solution stability but are still usable, while the solution The transparency was excellent. [Industrial Applicability]
[0184] The polyester-based pressure-sensitive adhesive composition of the present invention is an adhesive for electronic parts, an adhesive for bonding optical members, and the like. The polyimide of the present invention can be used as a pressure-sensitive adhesive, a pressure-sensitive adhesive for soft vinyl chloride, etc. Ester-based adhesives have excellent adhesion to substrates and can be given various functions. Since the refractive index can be increased, it can be suitably used for bonding optical components. can.
Claims
1. A pressure-sensitive adhesive sheet having a pressure-sensitive adhesive layer made of a polyester-based pressure-sensitive adhesive obtained by using a polyester-based pressure-sensitive adhesive composition containing a polyester-based resin (A) and an inorganic filler (B), wherein the polyester-based resin (A) is a polyester-based resin having a structural unit derived from a sulfonate group-containing dicarboxylic acid, the pressure-sensitive adhesive layer has a thickness of more than 10 μm and not more than 500 μm, the pressure-sensitive adhesive sheet has a release sheet provided on the outer side of the pressure-sensitive adhesive layer, and has an adhesive strength (α) of 5 N / 25 mm or more as described below. Adhesive strength (α): When a polyester-based adhesive is formed on a substrate to form an adhesive sheet, the sheet is attached to a glass plate adherend and left for 30 minutes at 23° C. and 50% RH. The 180° peel strength (N / 25 mm) from the adherend is then measured at a peel speed of 300 mm / min.
2. 2. The pressure-sensitive adhesive sheet according to claim 1, wherein the content of the inorganic filler (B) is 10 to 1000 parts by weight per 100 parts by weight of the polyester resin (A).
3. The adhesive sheet as described in claim 1 or 2, characterized in that the polyester-based adhesive composition further contains a hydrolysis inhibitor (C), and the hydrolysis inhibitor (C) is a compound having a carbodiimide group and an oxazoline group.
4. An adhesive sheet described in any one of claims 1 to 3, characterized in that the polyester-based adhesive composition further contains a crosslinking agent (D), and the crosslinking agent (D) is a polyisocyanate-based compound or a polyepoxy-based compound.
Citation Information
Patent Citations
Optical biaxially oriented polyester film and optical easy-adhesion film
JP2002137290A
Easily adhesive polyester film
JP2004285310A
Laminate
JP2009025575A
Adhesive composition, adhesive layer, adhesive tape, and double-sided adhesive tape
JP2015134906A
Adhesive polyester film laminate
JP2017094689A